PEMANFAATAN WEBSITE MADRASAH SEBAGAI MEDIA PEMBELAJARAN E-LEARNING DI TENGAH PANDEMI COVID-19 DI MTs KEDUNGJAMBE SINGGAHAN TUBAN - Mochamad Fathoni; Husniyatus Salamah Zainiyati (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2020)
Abstract The world is shocked by a global pandemic, known as covid-19 (Corona Virus Diseases-19). Almost all affected countries, including Indonesia. It affects all aspects of life, including education in Indonesia.Pemerintah enforce policies to work from home(WorkFromHome),worship at home, and learn at home. So that Teaching and Learning Activities (KBM) are replaced using online systems .  The application oflearning electronic(E-Learning) makes educators think seriously about the learning media that will be used. Various methods are used by Madrasas to facilitate these needs. One of them is making Madrasah Website as a learning tool that can be accessed by students from home.Keywords: Learning Media, E-Learning, Madrasa Website, Covid-19